2021
DOI: 10.1101/2021.03.14.21253547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with the stigma-discrimination complex towards healthcare workers among university students during the coronavirus pandemic in Mexico

Abstract: The COVID-19-related stigma towards healthcare workers negatively influences their performance and job satisfaction, and well-being. The frequency of COVID-19-related stigma towards healthcare workers and its associated factors has not been sufficiently investigated. The objective was to determine the frequency and variables associated with COVID-19-related stigmatisation towards health workers in emerging-age university adults in Mexico. Analytical and cross-sectional study using an online questionnaire in 1,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…As well, empirical evidence has shown an increasing number of healthcare personnel reporting being threatened, stigmatized, and socially discriminated against since the onset of the coronavirus outbreak (Cassiani‐Miranda et al . 2021; Sotgiu & Dobler 2020). A report from Jordan estimated that about 21% of healthcare workers (HCWs) experienced moderate levels of social discrimination, while 25% experienced a higher level of social discrimination (Dalky et al .…”
Section: Introductionmentioning
confidence: 99%
“…As well, empirical evidence has shown an increasing number of healthcare personnel reporting being threatened, stigmatized, and socially discriminated against since the onset of the coronavirus outbreak (Cassiani‐Miranda et al . 2021; Sotgiu & Dobler 2020). A report from Jordan estimated that about 21% of healthcare workers (HCWs) experienced moderate levels of social discrimination, while 25% experienced a higher level of social discrimination (Dalky et al .…”
Section: Introductionmentioning
confidence: 99%
“…A lot of investigations have been done in this regard to study help attitudes 37,38 . A study done in Mexico concluded that there is a considerable stigmatization of healthcare workers by the adult university students 39 . It has been shown that there is an increasing incidence that COVID-19 could be an independent risk factor for stress in healthcare workers 40 .…”
Section: Discussionmentioning
confidence: 99%